Model Structural Equation Modelling (Studi Kasus: Kenyamanan Emosional Pasien Kanker Anak Berdasarkan Healing Environment) - Nazihah Ekasari; Muhammad Mashuri; Bambang Widjanarko Otok; Anggra Ayu Rucitra (Jurnal Desain Interior, 2026)
Healthcare facilities play a crucial role in the patient recovery process. The condition of healthcare facilities has a direct impact on the psychological and emotional well-being of patients. Several previous studies have identified a relationship between the care environment and patient quality of life. Most studies employ literature reviews or observational methods to determine this relationship; however, to date, no quantitative measurements have been used to substantiate this relationship. Therefore, based on these issues, the effect of the healing environment on the quality of life of cancer patients, especially pediatric cancer patients, was analyzed using structural equation modeling (SEM). Data were collected through observation and questionnaires covering six factors that affect the quality of life of cancer patients at Hospital in Surabaya. PLS-SEM methods was used in the hope of obtaining a model of latent variable relationships with good accuracy. PLS SEM is a development of the SEM method, in which parameter estimation does not require specific distribution assumptions and can be performed on sample sizes.